2018
DOI: 10.1111/1346-8138.14722
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenitis suppurativa of the nape: Description of an atypical phenotype related to severe early‐onset disease in men

Abstract: Some patients with hidradenitis suppurativa (HS) develop severe inflammatory lesions of the nape. Through a single‐center, cross‐sectional study with a total of 377 patients, we sought to compare patients with and without nape involvement, to determine whether disease severity is greater in these patients and to describe their clinical characteristics. Thirty patients (90% male) were identified as having nape involvement. Patients with versus without nape involvement had greater disease severity, earlier disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…Commonly affected anatomic locations include the axillary, infra‐ and intermammary, inguinal, perineal, perianal and gluteal regions 39 . The lower abdomen, suprapubic, retroauricular, nape, eyelids and scalp are less frequently reported sites 40–42 . Patients may experience pain, itching, malodour, burning sensation and local warmth.…”
Section: Epidemiologymentioning
confidence: 99%
“…Commonly affected anatomic locations include the axillary, infra‐ and intermammary, inguinal, perineal, perianal and gluteal regions 39 . The lower abdomen, suprapubic, retroauricular, nape, eyelids and scalp are less frequently reported sites 40–42 . Patients may experience pain, itching, malodour, burning sensation and local warmth.…”
Section: Epidemiologymentioning
confidence: 99%
“…In analogy with HS involving the vulva, nape involvement is also associated with lower BMI patients, although mostly male, who fit into atypical LC2 and LC3 phenotypes. 15 Ultrasonographic study of the lesions demonstrated that most of them were fistulas with high Doppler signal suggestive of a high inflammatory load. Notably, most lesions of this type could have been mistakenly regarded as nodules or pustules, in accordance with previous publications that have demonstrated that ultrasonographic exam in HS patients can detect fistulas and abscesses more efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Those results point at VHS as a manifestation of the so‐called atypical HS as described by Naasan and Affleck 14 and posteriorly by Frew et al 13 Some other atypical sites of HS involvement include the nape. In analogy with HS involving the vulva, nape involvement is also associated with lower BMI patients, although mostly male, who fit into atypical LC2 and LC3 phenotypes 15 …”
Section: Discussionmentioning
confidence: 99%
“…4,5,8,9 • DCS and Nape HS: Pustules, nodules, abscesses, scars, and fistulas on the scalp or posterior cervical area. 3,10 • HS lymphedema: Persistent edema in patients with a history of HS in the same location after ruling out other etiologies. 11 3 | RESULTS…”
Section: Methodsmentioning
confidence: 99%
“…These characteristics were used as diagnostic criteria in the differential diagnosis with acne conglobate (AC), as it is described in the bibliography 4,5,8,9 DCS and Nape HS : Pustules, nodules, abscesses, scars, and fistulas on the scalp or posterior cervical area 3,10 HS lymphedema : Persistent edema in patients with a history of HS in the same location after ruling out other etiologies 11 …”
Section: Methodsmentioning
confidence: 99%